Demographic Characteristics, Comorbidities, and Length of Stay of COVID-19 Patients Admitted Into Intensive Care Units in Saudi Arabia: A Nationwide Retrospective Study - Al-Otaiby, Maram; Almutairi, Khalid M.; Vinluan, Jason M.; Al Seraihi, Ahad; Alonazi, Wadi B.; Qahtani, Mohammad Hassan; Aljeri, Thamer; Alhumud, Manal A.; Alobaidi, Nadhar; Alhurishi, Sultana A. (Frontiers in Medicine, 2022)
Background: This study aimed to describe the demographic characteristics and determine risk factors associated with disease severity and length of hospital and intensive care unit (ICU) stay in a cohort of COVID-19 patients admitted into ICU in Saudi Arabia. Methods: This was a national, multi-center, retrospective cross-sectional study of all COVID-19 cases admitted into different ICUs in Saudi Arabia between March 2020 and September 202l. Demographic, clinical features, comorbidities, and length of stay (LOS) data were retrieved from the national Health Electronic Surveillance Network (HESN) and Taqassi databases at the Saudi Ministry of Health (MOH) for subsequent analyses. We used multiple logistic regression models to determine risk factors associated with critical outcomes (including LOS in ICU) among COVID-19 cases. Results: A total of 12,436 COVID-19 patients were included in this study, with a mean age of 59.57 ± 18.30 years and 7679 (62%) less than 65 years old. COVID-19 was more common in males (N=7686, 61.9%) and Saudi nationals (N=8516, 68.5%). The clinical characteristic findings showed that 36.3% of patients required invasive ventilation whilst 65.4% received tracheostomies for ventilation, and 4% were on dialysis. Our analysis revealed that 2978 (23.9%) patients had one comorbidity, 4977 (47.4%) had two or more comorbidities, and diabetes (48.2%) was the most prevalent comorbidity, followed by hypertension (44.2%), and chronic cardiovascular disease (10.5%). Thirteen variables emerged as significant predictors of LOS in ICU using multiple linear regression analyses, with invasive ventilation as the strongest predictor of LOS in the ICU (beta=-0.68, p=0.001) and hospital admission (beta=-0.65, p=0.001). Conclusions: COVID-19 continues to affect millions of people around the world, with a mortality rate of about 2–3% of all infected patients. Our analysis revealed that comorbidities such as chronic kidney disease, cardiovascular disease, diabetes, and older age were significant risk factors associated with a poorer prognosis and longer duration of stay in hospitals and ICU.